Severity of coeliac disease and clinical management study when using a CYP3A4 metabolised medication: a phase I pharmacokinetic study. Issue 3 (4th March 2020) - Chretien, Marc L; Bailey, David G; Asher, Linda; Parfitt, Jeremy; Driman, David; Gregor, Jamie; Dresser, George K
Abstract : Objective: Severity of coeliac disease depends in part on the extent of small intestinal mucosa injury. Patients with the most abnormal pathology have loss of duodenal villi CYP3A4, a drug-metabolising enzyme that inactivates many drugs. These patients are hypothesised to have greater systemic concentrations of felodipine, a drug which normally has low oral bioavailability secondary to intestinal CYP3A4-mediated metabolism. It serves as a representative for a class containing many medications. Design: A phase I, open-label, single-dose, pharmacokinetic study. Setting: London, Ontario, Canada. Participants: Patients with coeliac disease (n=47) with positive serology and healthy individuals (n=68). Main outcome measures: Patients with coeliac disease—upper gastrointestinal endoscopy and oral felodipine pharmacokinetics study within a 3-week period. Healthy individuals—oral felodipine pharmacokinetics study with water and grapefruit juice. Results: Coeliac stratification categories: Group A (n=15, normal), B+C (n=16, intraepithelial lymphocytosis with/without mild villous blunting) and D (n=16, moderate/severe villous blunting). Groups A, B+C and D had linear trends of increasing felodipine AUC0–8 ; mean±SEM, 14.4±2.1, 17.6±2.8, 25.7±5.0; p<0.05) and Cmax (3.5±0.5, 4.0±0.6, 6.4±1.1; p<0.02), respectively. Healthy subjects receiving water had lower felodipine AUC0 – 8 (11.9±0.9 vs 26.9±0.9, p=0.0001) and Cmax (2.9±0.2 vs 7.7±0.2, p=0.0001) relative to those receiving grapefruit juice. Conclusions: Increased felodipine concentrations in patients with coeliac disease were most probably secondary to decreased small intestinal CYP3A4 expression. Patients with severe coeliac disease and healthy individuals with grapefruit juice had equivalently enhanced effect. Thus, patients with severe coeliac disease would probably experience similarly altered drug response, including overdose toxicity, from many important medications known to be metabolised by CYP3A4. Patients with coeliac disease with severe disease should be considered for other clinical drug management, particularly when there is the potential for serious drug toxicity.